ANALISIS PRODUKTIVITAS TENAGA KERJA PADA PENGOLAHAN KOPRA DI KOTA RAHA - La Idin, La Idin (JURNAL EKONOMI UHO, 2016)
This study aims to find out the determinant of labor productivity of  copra industry  in Kusambi and Napano Kusambi District Raha City. This research analyzed through descriptive analysis. Sampel of this research is 12 labor, 8 labor of Kusambi District from 4 unit factory and 4 labor of Napano Kusambi District from 2 unit factory. The finding showed that labor productivity of Kusambi District higer than  labor productivity of Napano Kusambi District. Determinant of labor productivity of   copra industry  in Raha City is training of labor. Labor participation proportion in training of copra production for Kusambi District is  62,5 percent; and for Napano Kusambi District is 50 percent.